Post-concussion return to boxing protocol - Sethi, N (South African Journal of Sports Medicine, 2016)
Background: Concussion is a complex pathophysiological process affecting the brain, induced by traumatic biomechanical forces. Immediately following a concussion, an athlete is usually advised physical and cognitive rest until post-concussion symptoms abate. The athlete then enters a stepwise return-to-play protocol. Premature return to play risks a second concussion, second impact syndrome, exacerbation and persistence of post-concussive symptoms. Various sports governing organisations such as the National Football League have developed post-concussion return to play protocols. Discussion: Professional boxing is a popular contact sport in which concussions are common. Professional boxing currently lacks a standardised post-concussion return to boxing protocol. Professional boxers are arbitrarily suspended for periods ranging from 30 to 90 days after suffering a technical knockout (TKO) due to multiple head and body shots or after a knockout (KO). For some boxers a neurology clearance is requested prior to their return to boxing. Conclusion: Developing and implementing a post-concussion return to the boxing protocol will standardise a return to boxing decision-making process and help to protect a boxer’s health. This paper proposes a post-concussion return to boxing protocol with the recommendation that the proposed protocol be debated vigorously by the scientific community and evidence-based guidelines be developed by the medical community in conjunction with the professional boxing governing bodies.